Evaluación de los efectos de croton lechleri en la candidiasis vulvovaginal - León Hoyos, Félix Ajejandro (2018)
Introduction: The aims of the present study were to determine and compare the side effects of Croton lechleri and clotrimazole cream 1% in the treatment of vulvovaginal candidiasis in patients at the health center Pillcomarka District, Huánuco. Methods. Were selected for study thirty patients, women of childbearing age with symptoms of vulvovaginal candidiasis and pseudomicelos observation in microscopy. It was assigned to female patients non-aleatory into 2 groups of topical treatment; one group received Croton lechleri and the other received clotrimazole cream 1%. We extracted a sample of blood and urine before beginning and end of treatment. Results. We were included 30 patients in this research work. Of the total referrals leukorrhea 44.4% belonged to experimental group (croton) and 55.6% belonged to control group (clotrimazole) [OR = 8.68 (95% CI 0.41, 184.28) p <0, 22)], and pruritus referrals 44.4% belonged to experimental group and 55.6% belonged to control group [OR = 8.68 (95% CI 0.41, 184.28) p <0, 22)]. With respect to non-pathological microscopic examination 44.4% belonged to experimental group and 55.6% belonged to control group [OR = 0.20 (95% CI 0.02, 2.05) p <0.22)] and all non-pathological cultives 46.4% belonged to experimental group and 53.6% belonged to control group [OR = 0.24 (95% CI 0.03, 3.13) p <0.41)]. The posttreatment results of blood tests and urine examination did not show significant differences as well as in the experimental group and control group. Conclusions. There were no significant differences in post-treatment results from the use of croton against the use of clotrimazole